The Application of Integral Equations to the Numerical Solution of Nonlinear Singular Perturbation Problems (Journal of Computational Mathematics, 1994)
The nonlinear singular perturbation problem is solved numerically on non-equidistant meshes which are dense in the boundary layers. The method presented is based on the numerical solution of integral equations [1]. The fourth order uniform accuracy of the scheme is proved. A numerical experiment demonstrates the effectiveness of the method.